Doppler assessment of throphoblastic blood flow to predict adverse pregnancy outcome - A. V. Pomortsev; J. Yu. Dyachenko; M. A. Matosyan (Инновационная медицина Кубани, 2020)
Objective. To evaluate the diagnostic utility of trophoblastic blood flow Doppler parameters in predicting an adverse pregnancy outcome.Material and Methods. This was a retrospective study of 218 pregnancies of women between 8 and 11 weeks’ gestation. Depending on the pregnancy outcome, patients were divided into 4 clinical groups. All women underwent an ultrasound examination using Voluson S8, Voluson E8 with high-quality grey scale, color flow mapping and pulsed-wave Doppler modes. We used a program for obstetric research with the following instrument settings: 100 MHz Doppler frequency, thermal index (TI) was <1, mechanical index (MI) was 1. The examination time did not exceed 20 minutes. There was no radiation exposure. Transvaginal and transabdominal sonographies were performed.Results. To form a risk group for an adverse fetal outcome due to fetoplacental insufficiency, it is necessary to identify ultrasound markers of inadequate placental perfusion by means of a Doppler study of fetoplacental blood flow. For this purpose, we examined 218 pregnancies of women between 8 and 11 weeks’ gestation to determine the diagnostic utility of various parameters: resistivity index, pulsatility index, systolic/diastolic ratio and chorionic vascularization index (k, %). We received results proving high sensitivity (76.9%) and specificity (89.7%) of the chorionic vascularization index (k, %), as well as low specificity (54.7%) and high sensitivity (81.5%) of trophoblastic blood flow resistivity index.Conclusion. Thus, the chorionic vascularization index (k, %) is of high diagnostic utility for predicting an adverse fetal outcome.